Dimensões da república das letras no Amazonas: a intelectualidade Gymnasiana em Manaus (1900-1930) - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This dissertation intends to analyze the trajectory of middle-class gymnasianos students of Manaus (capital of Amazonas, Brazil) in the literate world, addressing some barriers in the foundation of the educational system during the transition from Empire to the Republic through the gymnasiana student press that publicized the political and ideological militancy of the class. Thereby, it has been used an investigational procedure that associates national and regional context. In 1915, obstacles to changes in education have become the target of protests by gymnasianos involved with the student press, whether they were in favor or against the local oligarchies. In 1930, in retaliation to the police, a riot was triggered by the gymnasianos , it was instigated by the remaining students through the local newspaper and became known as the Gymnasiana revolution of 1930 . Therefore, the consulted documentation, such as newspapers, school surveys, reports, government messages, among others, has allowed us to question the consensus between some historians and local writers about this event.
Keywords: Manaus (AM); Primeira República; Ensino secundário; Instrução pública; Imprensa Gymnasiana; Vida intelectual; Manaus (AM), History, First Republic; Secondary Education; Public Instruction; Press Gymnasiana; Intellectual life; CIÊNCIAS HUMANAS: HISTÓRIA